Pemanfaatan Sistem Informasi Manajemen Sebagai Alat Pengendalian Dan Pengambilan Keputusan Strategis - Bagusman, Chajarara; Nasution, Muhammad Irwan Padli (CV. SINAR HOWUHOWU, 2025)
This study discusses the utilization of Management Information Systems (MIS) as a tool for control and strategic decision-making in modern organizations. Along with the rapid advancement of information technology, MIS has evolved beyond its traditional role as an operational data provider to become a core foundation for managerial planning, supervision, and strategic policy formulation. Through the integration of accurate, relevant, and real-time data, organizations can strengthen internal control mechanisms and enhance evidence-based decision- making processes. The strategic implementation of MIS enables efficiency, transparency, and competitiveness while supporting adaptive management in dynamic business environments. This paper highlights that effective use of MIS is essential for organizations aiming to achieve sustainable growth and operational excellence in the digital era.